2018
DOI: 10.1111/jocn.14557
|View full text |Cite
|
Sign up to set email alerts
|

Triggers and decision‐making patterns for receiving total knee arthroplasty among older adults with knee osteoarthritis: A qualitative descriptive study

Abstract: Our findings provide evidence for healthcare providers to offer information and support to their older adult patients with knee-osteoarthritis pain who are deciding whether to undergo total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Participants discussed how the impact of OA on their lives and the failure of prior treatments prompted them to consider injections. The influence of ineffective prior treatments has been described as a motivating factor for patients who undergo TKR as well (17). A study by Selten et al demonstrated that participants were most concerned about a treatment's efficacy, accessibility, and potential side effects (10), which are concerns that our participants shared.…”
Section: Discussionmentioning
confidence: 78%
“…Participants discussed how the impact of OA on their lives and the failure of prior treatments prompted them to consider injections. The influence of ineffective prior treatments has been described as a motivating factor for patients who undergo TKR as well (17). A study by Selten et al demonstrated that participants were most concerned about a treatment's efficacy, accessibility, and potential side effects (10), which are concerns that our participants shared.…”
Section: Discussionmentioning
confidence: 78%
“…17,21,64,67,79,93,114,117,120,137,140,159,164 We included findings from 118 reports (105 unique samples) published between 1998 and 2021. 1–5,7,9–13,15,16,18,20,22–27,31 , 33,34,37,39,40,43-46,48,49 , 52–58,60,61,63,65,66,68–78 , 80-82,86-92,94-101 , 103–105,108–110,112,113,115,118,119 , 121,122,124-130,132-134,141-147 , 149–155,158,160–162,165–169 Table 2 presents the author, year of publication, country, condition, number of participants, and age. Most studies explored the experience of knee and hip osteoarthritis, and 30 of these specifically aimed to understand decision-making for hip or knee joint replacement surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, knee pain VAS was shown to be an independent predictive factor for determining whether to have surgery in adjusted multivariate logistic regression analysis. Previous studies have shown that the main triggers for undergoing TKA are severe pain and inability to walk [ 5 ]. Osteoarthritic pain affected their daily life including activities, mood, walking ability, and social activities [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reaching this threshold defines the decision-making process [ 4 ]. However, previous studies did not distinguish between medial or lateral tibiofemoral (TF) OA, and there has been no analysis of objective decision-making factors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%